Studi Penggunaan Pupuk Hayati Pada Tanaman Kedelai - Misran, Misran (Jurnal Penelitian Pertanian Terapan, 2013)
Study of the use of biological fertilizers on soybean. One of the efforts to improve the growth and yield of soybean is to utilize biological fertilizer in the form of inoculants, both root nodule bacteria and endophytic bacteria. Assessment carried out on land formerly used for rice cultivation in Palangki, District Ampek Nagari, Sijunjung regency, West Sumatra, in the dry season (June to September 2010). The design used was a randomized block design (RBD) with 4 treatments and 4 replications, plot size of 5 x 4 m, using Anjasmoro soybean varieties, spacing of 40 x 10 cm, each planted 2 seeds / hole. Treatment in this study, namely: Land given lime without bacterial inoculation (A1); Land without lime, and soy beans inoculated bacteria (A2); Land given lime and soy beans inoculated bacteria (A3); and Land sown with soybean planting land former, given lime and seeds not inoculated bacteria (A4). Data were collected for plant height, number of primary branches, total number of pods, number of pods, amount number of seeds, seed fresh weight and dry weight of seeds. The study showed that treatment of ex-land sprinkled with soybean planting, and seeds were not inoculated lime and (A4) gives the highest response for each parameter of observation compared with other treatments. Keywords: soybean, bio-fertilizers, bacteria.